2023
DOI: 10.3389/fmicb.2023.1128668
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Stevioside on Streptococcus mutans and Candida albicans dual-species biofilm

Abstract: IntroductionStreptococcus mutans is the most prevalent biofilm-forming pathogen in dental caries, while Candida albicans is often detected in the presence of S. mutans.MethodsWe aimed to evaluate the anti-caries effect of stevioside in medium trypticase soy broth (TSB) with or without sucrose supplementation compared with the same sweetness sucrose and xylitol in a dual-species model of S. mutans and C. albicans, based on planktonic growth, crystal violet assay, acid production, biofilm structural imaging, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…It was found to inhibit the growth and biofilm formation of various bacteria, including S. mutans, Borrelia burgdorferi, Lactobacillus, and coagulase-negative staphylococci [29,37,38]. Furthermore, a study by Guo et al demonstrated the inhibitory effects of stevioside on a dual-species biofilm model of S. mutans and Candida albicans [39], highlighting its potential against fungal species. In addition to inhibiting biofilm formation, stevia has also been shown to reduce EPS production [26,29], suggesting its ability to interfere with the structural integrity and protective properties of biofilms, making them more susceptible to disruption and removal.…”
Section: Discussionmentioning
confidence: 99%
“…It was found to inhibit the growth and biofilm formation of various bacteria, including S. mutans, Borrelia burgdorferi, Lactobacillus, and coagulase-negative staphylococci [29,37,38]. Furthermore, a study by Guo et al demonstrated the inhibitory effects of stevioside on a dual-species biofilm model of S. mutans and Candida albicans [39], highlighting its potential against fungal species. In addition to inhibiting biofilm formation, stevia has also been shown to reduce EPS production [26,29], suggesting its ability to interfere with the structural integrity and protective properties of biofilms, making them more susceptible to disruption and removal.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 10 % acesulfame-K and 7.5 % sucralose inhibited the biofilm formation of Porphyromonas gingivalis , an anaerobic periodontal pathogen, and showed bactericidal activity against bacteria within the biofilm [ 88 ]. Stevioside also inhibited the formation of mixed biofilms of C. albicans and S. mutans and acid production [ 29 ]. Stevioside facilitated the metabolic utilization of galactose and intracellular polysaccharides while reducing that of sucrose.…”
Section: Role Of Sweeteners In Oral Biofilm Modulationmentioning
confidence: 99%
“…Although non-nutritive sweeteners cannot be digested to generate energy, they can be potentially toxic to cells following cellular absorption [ 25 ]. Nevertheless, non-nutritive sweeteners have also been shown recently to be beneficial in managing microbial infections [ [26] , [27] , [28] , [29] , [30] ]. Bulk sweeteners also exhibit antibacterial efficacy against a variety of drug-resistant pathogens [ [31] , [32] , [33] ].…”
Section: Introductionmentioning
confidence: 99%
“…In the quest for sugar substitutes that could prevent for caries, one research has indicated that stevioside significantly inhibits growth and biofilm formation in mixed-species cultures, suggesting its potential as an alternative to sucrose [ 44 ]. Interestingly, the addition of 1% sucrose to these cultures counteracted the inhibitory effects of stevioside, highlighting the importance of reducing sucrose intake for dental caries management [ 44 , 82 ].…”
Section: The Influence Of External Factors On Oral Microbiomesmentioning
confidence: 99%
“…In the quest for sugar substitutes that could prevent for caries, one research has indicated that stevioside significantly inhibits growth and biofilm formation in mixed-species cultures, suggesting its potential as an alternative to sucrose [ 44 ]. Interestingly, the addition of 1% sucrose to these cultures counteracted the inhibitory effects of stevioside, highlighting the importance of reducing sucrose intake for dental caries management [ 44 , 82 ]. Among various commercially available sugar substitutes, stevioside, along with other levorotatory carbohydrates such as xylitol and sorbitol, has demonstrated similar inhibitory effects on the mixed-species biofilm [ 83 ].…”
Section: The Influence Of External Factors On Oral Microbiomesmentioning
confidence: 99%